Church and State in Bourbon Mexico: The Diocese of Michoacán, 1749-1810. By David A. Brading. Cambridge: Cambridge University Press1994. Pp. 300. $59.95. ISBN: 0-521-46092-1. - Juárez, José Roberto (Journal of law and religion, 2001)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0748081400007451/resource/name/firstPage-S0748081400007451a.jpg